Impact of fines and rock wettability on reservoir formation damage - Al-Yaseri, A.; Al Mukainah, H.; Lebedev, M.; Barifcani, Ahmed; Iglauer, S. (Wiley-Blackwell, 2016)
Pore throat plugging of porous rock by fine particles causes formation damage, and thus has attracted attention in various areas such as petroleum engineering, hydrology and geothermal energy production. Despite significant efforts, the detailed pore-scale mechanisms leading to formation damage and the associated permeability reduction are not well understood. We thus investigated plugging mechanisms and characteristics with a combination of ex situ (i.e., coreflooding measurements and scanning electron microscopy imaging) and in situ (i.e., nuclear magnetic resonance and µCT) methods, with a particular focus on the effect of wettability. The corefloods indicated that permeability drops rapidly when fines are injected; mechanistically thin pore throats are plugged first, followed by filling of adjacent pore bodies with the fine material (as evidenced by the nuclear magnetic resonance and µCT experiments, which can measure the pore size distribution evolution with fines injection). Furthermore, it is clear that wettability plays a major role: if fines and rock wettability are identical, plugging is significantly accelerated; wettability also controls the 3D distribution of the fines in the pore space. Furthermore we note that the deposited fines were tightly packed, apparently due to strong adhesion forces.